2018
DOI: 10.1159/000492377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increased Convection Volume by Mid-Dilution Hemodiafiltration on the Subclinical Chronic Inflammation in Maintenance Hemodialysis Patients

Abstract: Mid-dilution hemodiafiltration (MID) is a dialytic technique that might improve systemic inflammation of patients in chronic hemodialysis (HD) by increasing substitution volumes. To verify this hypothesis, we performed a prospective cross-over study comparing the effect on inflammatory biomarkers of higher convection by MID versus standard convection by post-dilution hemodiafiltration (HDF). Patients under chronic HD were therefore treated by MID and HDF by crossover design. Each treatment period lasted 4 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Gan and Zhou conducted a study on FGF23 and Klotho in 180 patients with CKD‐mineral bone disorder. They observed that in HD patients, especially those with secondary hyperparathyroidism, the levels of FGF23 were high and levels of Klotho were low: this predisposed for greater ectopic calcifications, which are known to be typically present in patients in chronic renal diseases even before undergoing dialysis treatment and suggested a significant correlation with increasing volume of the left ventricle and cardiac hypertrophy . The pro‐fibrotic action of FGF23 on the heart has recently been documented, using cardiac autopsies from 24 patients on HD and in vitro studies.…”
Section: Risk Related To the Increase In Fgf23 Serum Levelsmentioning
confidence: 99%
“…Gan and Zhou conducted a study on FGF23 and Klotho in 180 patients with CKD‐mineral bone disorder. They observed that in HD patients, especially those with secondary hyperparathyroidism, the levels of FGF23 were high and levels of Klotho were low: this predisposed for greater ectopic calcifications, which are known to be typically present in patients in chronic renal diseases even before undergoing dialysis treatment and suggested a significant correlation with increasing volume of the left ventricle and cardiac hypertrophy . The pro‐fibrotic action of FGF23 on the heart has recently been documented, using cardiac autopsies from 24 patients on HD and in vitro studies.…”
Section: Risk Related To the Increase In Fgf23 Serum Levelsmentioning
confidence: 99%